G4 Structures in Control of Replication and Transcription of rRNA Genes - Havlová, Kateřina; Fajkus, Jiří (Frontiers in Plant Science, 2020)
Genes encoding 45S ribosomal RNA (rDNA) are known for their abundance within eukaryotic genomes and for their unstable copy numbers in response to changes in various genetic and epigenetic factors. Commonly, we understand as epigenetic factors (affecting gene expression without a change in DNA sequence) namely DNA methylation, histone posttranslational modifications, histone variants, RNA interference, nucleosome remodelling and assembly, and chromosome position effect. All these were actually shown to affect activity and stability of rDNA. Here we focus on another phenomenon - the potential of DNA containing shortly spaced oligo-guanine tracts to form quadruplex structures (G4). Interestingly, sites with a high propensity to form G4 were described in yeast, animal, and plant rDNAs, in addition to G4 at telomeres, some gene promoters, and transposons, suggesting the evolutionary ancient origin of G4 as a regulatory module. Here we present examples of rDNA promoter regions with extremely high potential to form G4 in two model plants, Arabidopsis thaliana and Physcomitrella patens. The high G4 potential is balanced by the activity of G4-resolving enzymes. The ability of rDNA to undergo these “structural gymnastics” thus represents another layer of the rich repertoire of epigenetic regulations which is pronounced in rDNA due to its highly repetitive character.